1996
DOI: 10.1038/ki.1996.265
|View full text |Cite
|
Sign up to set email alerts
|

The hyperfiltration theory: A paradigm shift in nephrology

Abstract: Experimental studies incriminate glomerular hypertension in mediating progressive renal damage after any of a variety of initiating injuries. Prevention of glomerular hypertension by dietary protein restriction or antihypertensive therapy lessens progressive glomerular damage in several experimental models of chronic renal disease. Glomerular hypertension and hyperfiltration also occur in humans with diabetes mellitus, solitary or remnant kidneys, and various forms of acquired renal disease. Clinical studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
556
3
34

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 754 publications
(613 citation statements)
references
References 45 publications
20
556
3
34
Order By: Relevance
“…To the extent that AGE accumulation is a strong predictor of adverse renal outcomes in patients with diabetes, it is possible to speculate that reduced nephron endowment may be associated with accelerated AGE accumulation, and therefore more aggressive renal disease, in the setting of diabetes. This is consistent with the Brenner hypothesis, which links the observed association of reduced nephron number with the subsequent increased risk of renal disease in adults [18]. In support of this concept, Jones et al report exacerbated renal and glomerular hypertrophy in adult LPD rat offspring following induction of streptozotocininduced diabetes and that these glomerular abnormalities persist even when insulin is administered [28].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…To the extent that AGE accumulation is a strong predictor of adverse renal outcomes in patients with diabetes, it is possible to speculate that reduced nephron endowment may be associated with accelerated AGE accumulation, and therefore more aggressive renal disease, in the setting of diabetes. This is consistent with the Brenner hypothesis, which links the observed association of reduced nephron number with the subsequent increased risk of renal disease in adults [18]. In support of this concept, Jones et al report exacerbated renal and glomerular hypertrophy in adult LPD rat offspring following induction of streptozotocininduced diabetes and that these glomerular abnormalities persist even when insulin is administered [28].…”
Section: Discussionsupporting
confidence: 68%
“…In the Brenner hypothesis, one of the key links between reduced nephron endowment and renal disease is systemic hypertension [18]. In a carefully conducted stereological autopsy analysis of kidneys, Keller et al demonstrated that patients with primary hypertension had fewer glomeruli per kidney than their normotensive controls [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A reduction in the number of functional nephrons, whether induced genetically, surgically, or by acquired renal disease, contributes to the progression of CKD, likely secondary to glomerular hyperfiltration and hypertrophy. 2 However, the precise mechanism that mediates the progression of CKD in these patients remains unclear.…”
mentioning
confidence: 99%
“…Essa hiperfiltração leva à esclerose glomerular e proteinúria (Brenner et al 1996). A proteinúria tem sido considerada um importante fator na progressão da DRC em humanos (Willians et al 1988), em cães (Jacob et al 2005) e em gatos (Syme et al 2006).…”
unclassified